A Rare Case of Malignant Tumor of the Larynx with Good Prognosis: Laryngeal Chondrosarcoma - Abderrahim Elktaibi; Issam Rharrassi; Nabil Hammoune; Youssef Darouassi; Mohammed Amine Hanine; Haddou Ammar (Case Reports in Oncological Medicine)
Laryngeal chondrosarcoma is a rare laryngeal tumor that most frequently originates from the cricoid cartilage. The majority of lesions are low grade and the distinction from benign chondromas must be made. We present a case of a laryngeal chondrosarcoma arising from the cricoid cartilage in a 75-year-old Arab man who presented with hoarseness, dysphonia, and dyspnea. Endoscopic and radiological examinations showed a mass of the wall of his larynx with displaced structures, airway obstruction, and destruction of the cartilage. The patient underwent total laryngectomy. Histological examination supported the diagnosis of low-grade chondrosarcoma. Five months later, the radiological and clinical findings showed no evidence of recurrence or metastases. Laryngeal chondrosarcomas remain a rare disease of unknown etiology, with slow and insidious symptoms. The treatment is surgical, given the importance of preserving the larynx to patients’ quality of life. The prognosis is favorable and metastases rarely occur.